Determination of martensite structures of the Au7Cu5Al4 and Au7Cu5.7Al3.3 shape-memory alloys - Elcombe, M.; Kealley, Cat; Bhatia, V.; Thorogood, G.; Carter, Damien; Avdeev, M.; Cortie, M. (Pergamon, 2014)
The β-phase of Au7Cu5Al4 undergoes a reversible shape-memory phase transformation for which several conflicting martensite phases have been reported. Here we show the significance of the cooling temperature used to obtain the martensite. If Au7Cu5Al4 is cooled from the parent phase condition to cryogenic temperatures, e.g. below 200 K, the martensitic phase is orthorhombic (space group Pcmn, a = 4.4841 Å, b = 5.8996 Å, c = 17.8130 Å); however, when this composition is cooled to only ~260 K it will in general consist of a mixture of orthorhombic and monoclinic phase (the latter has space group P21/m, a = 4.4742 Å, b = 5.9265 Å, c = 13.3370 Å, β = 91.425°). In contrast, a sample with decreased Al content (Au7Cu5.7Al3.3) transforms fully to monoclinic phase if cooled to ~260 K.